PERAN DAN FUNGSI DEWAN PENGAWAS SYARIAH (SHARI’A SUPERVISORY BOARD) DALAM PERBANKAN SYARIAH DI INDONESIA - Rahmawati, Nikmah (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
Shariâ??a Supervisory board (DPS) is basically the extension of National Shariâ??a Board (DSN) in realizing the religious advices instructed by National Shariâ??a Board (DSN). Shariâ??a Supervisory Board (DSN) plays as the supervisor of Shariâ??a financial institutions like Shariâ??a Bank, Shariâ??a insurance, Shariâ??a money market, etc ini order that such all institutions run in accordance with the demand of Islamic Shariâ??a. Supervision is either on the basis of Shariâ??a financial products or the management and the administration of Shariâ??a financial institutions, which matches with the Shariâ??a. DPS isnâ??t involved directly in the managerial practice of Shariâ??a financial institutions because it has been the responsibility, directly, under the directorateâ??s authority of a Shariâ??a financial institutions, but DPS has the right to give input toward the managers of the institutions. There are still more Shariâ??a financial institutions such as Shariâ??a bank, which hasnâ??t yet benefit maximally the rule and the function of DPS in its institution. More over, the improvement of professionalism for DPSâ??s members in performing the community mandate is not maximal yet. Requested on the future, DPS does become an institution, which is able to empower its rule and function for the development of Shariâ??a banking in Indonesia.